Die Geodätische Lagemessung über das Grönländische Indlandeis der Internationalen Glaziologischen Grönland-Expedition (EGIG) 1959. - Hofmann, Walther (Meddelelser om Grønland, 1964)
The present report deals with the geodetic work done by the group "Lagemessung" of the International Glaciological Greenland-Expedition (EGIG) during the summer campaign 1959 and with its evaluation and results. This work was aimed to procure the basis for the determination of movement and strain of the ice surface in two big profiles over the Greenland Ice Cap by precise measurements of fixed points (markers). The main profile extends over 925 km from the west coast of Greenland at Atâ Sund to the east coast near Cecilia Nunatak; in this profile, 79 markers were established with an average distance of 11.5 km. The second profile of 330 km length runs in north-south-direction in a distance of about 100 km parallel to the west coast; it contains 36 markers (average distance 8.9 km) and crosses the West-East-Profile in the Point Carrefour. The markers are aluminium tubes with 62 mm diameter; when established, they rose in the West-East-Profile and in the southern section of the North-South-Profile (south of Carrefour) 7 m above the snow surface, in the remaining North-South-Profile only 5 m. The main procedure of the geodetic work was the electronic distance measurement with the Tellurometer. It was applicated for pure trilateration in quadrangles with diagonals in the W-E-Profile, and for distance measurement in traverses in the marginal zones and in the N-S-Profile. The base of the quadrangles coincided with the W-E-profile; it joined two of the markers there established. The covering line was approximately parrallel to the W-E-profile. Its endpoints were not marked. As the group was equipped with 4 Weasels, 3 Master and 3 Remote Stations of the Tellurometer, the complete measurement of one quadrangle was possible in one putting-up. The Tellurometer sets were modified for the use under arctic conditions by preparatory measures; the original Power Pack was replaced by a built-in transistorized converter (Chapter II). Having overcome certain difficulties, the measurements were carried out in both profiles according to plan (Chapter III). It proved to be necessary to set up two neighbouring stations in the W-E-Profile respectively to the crests of the ice waves because the Tellurometer measurement was not able to overleap these waves. But under terrain conditions favorable for the measurement the Tellurometer yielded the distances with the unexpectedly high accuracy of ± 5 cm. This accuracy results from the adjustment of related observations in the redundant quadrangles with diagonals (Chapter IV). Originally, the signs of the discrepancies in the quadrangles showed a considerable one-sidedness; this indicated a systematical influence which was not eliminated by the reduction. lt seems that only a retardation of the transit time in distances of small clearance which can be proved also theoretically cornes into question for this phenomenon. The systematic portion of the discrepancies was eliminated by subsequent reduction (Chapter IV, Section 6). Two base lines for the calibration of future measurements were established and measured at the endpoints of the W-E-Profile in Qapiarfît and Cecilia Nunatak (Chapter III, Section 8). The reduction and the adjustment of the measurements (Chapter IV) yielded the oblique distances and angles between the markers (Chapter V). They are the fundament for the comparison after the repetition of the measurements in an adequate time interwall. For this comparison, a method based on the addition of displacement vectors is developed and tested in a marginal profile section for which double measurements with a time intervall of 3 months existed (Chapter V, Section 8). The total expansion of this section of ca. 36 km is 9 m. But this expansion is distributed very irregularly over the 4 distances between markers of approximately equal length forming the section. Approximate geographical coordinates of the markers at the International Earth Ellipsoid were computed from the horizontal distances at sea level and the azimuts of the profile members (Chapter VI). The comparison of the geodetically determined coordinates of the main points in the profile with the astronomical ones shows systematic differences, caused presumably by the ice movement during the measuring time. As the glaciological meaning of the measurements will be achieved only by the repetition, also geodetic results in the sence of precise determination of positions can be expected only after this repetition.